2016
DOI: 10.1021/acs.nanolett.6b01218
|View full text |Cite
|
Sign up to set email alerts
|

Polaron Stabilization by Cooperative Lattice Distortion and Cation Rotations in Hybrid Perovskite Materials

Abstract: Solution-processed organometallic perovskites have rapidly developed into a top candidate for the active layer of photovoltaic devices. Despite the remarkable progress associated with perovskite materials, many questions about the fundamental photophysical processes taking place in these devices, remain open. High on the list of unexplained phenomena are very modest mobilities despite low charge carrier effective masses. Moreover, experiments elucidate unique degradation of photocurrent affecting stable operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
325
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(348 citation statements)
references
References 56 publications
22
325
1
Order By: Relevance
“…According to the literature, continuous 1-sun illumination will generate a quasi-static charge state by lattice distortion and phase separation. These states will be accumulated and coexist with photo-generated carriers, leading to current degradation during further 1-sun light soaking22626364.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, continuous 1-sun illumination will generate a quasi-static charge state by lattice distortion and phase separation. These states will be accumulated and coexist with photo-generated carriers, leading to current degradation during further 1-sun light soaking22626364.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest longer UV exposure can change UV degradation/recovery mechanism. Light-induced meta-stable trap states226263 and holes accumulation65 can have rules in UV degradation/recovery.…”
Section: Discussionmentioning
confidence: 99%
“…There is an on-going debate about electron and hole mobilities in organic-inorganic perovskites, 15,16,18,19 while only one theoretical study exists for inorganic ones 79 . As far as the organic-inorganic ones are concerned, Zhu and Podzorov 18 have suggested that charge carriers may be protected by the formation of a large (heavy) polaron, which could also explain the modest charge carrier mobilities.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations concern the organic-inorganic perovskites but carrier mobilities appear to be significantly higher in inorganic ones, which hints to different charge transport properties 7,80,81 . Using the hybrid density functional theory, Neukirch et al 79 found that in a CsPbI 3 cluster electron and hole polarons are formed, with a larger BE for the electrons. This seems to fit with the conclusion of a weakly localized exciton in organic-inorganic perovskites proposed by He et al ., 30 which they attributed to band tail states, mainly due to electrons at the bottom of the CB.…”
Section: Discussionmentioning
confidence: 99%
“…We used norm-conserving PBE pseudopotential including d core states of Pb and sampled an unshifted (8 × 8 × 8) grid in BZ for geometry optimization and for electronic calculation at energy cutoff of 80 Ry for PSCs containing organic cations and 100 Ry for CsPbI 3 . Because lattice distortion is not significantly affected by types of functional and spin-orbit coupling, [42] we used PBE exchange functional. We used DFPT for phonon dispersions and considered the non-analytic term of dynamical matrix at Γ of BZ to account for LO-TO splitting.…”
Section: Various Types Of Configurations Of A-site Cations With Surromentioning
confidence: 99%